Pengaruh Financial Technology Terhadap Pendapatan UKM di Bogor - Yayuk Nurjanah; Toni Andrianto (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
Financial technology (fintech) is an innovation in the field of financial services which is a service to access financial resources easily and quickly. Business actors can use fintech as a tool to help finance capital, digital payment services and financial management. Local business or UKM currently have difficulties in terms of digital payment services and financial arrangements with fintech being able to overcome this. The role of fintech is not only limited to commercial capital financing but can also expand to various aspects such as digital payment services and financial management. This study aims to determine the effect of financial technology proxied by digital payments and financial management on income. The method of analysis used multiple linear regression. The sample in this study were 124 UKM in Bogor. This study reveals that digital payments and financial management have a positive and significant effect on income.